CULTURE VALUE AND FAMILY CONNECTIONS IN VIETNAMESE ADVERTISING (Proceedings of the World Conference on Media and Mass Communication, 2023)
Family connections were used in advertising. Numerous research has also uncovered the significance of cultural values and familial feelings in advertising. As a result, advertisers exploit a variety of cultural and familial links in their advertisements and rely on cultural values to arouse this feeling in viewers. Diverse cultures have explored this model. The use of this strategy in advertising in Vietnam, a collectivist country, has received little research, nevertheless. In order to support the idea that advertising that actively integrates Vietnamese cultural values has an effect on audiences' families, we looked at pertinent case studies. The study focuses on demonstrating how advertisers use cultural elements to sway the emotions of their target audiences. Content analysis is employed in our study to demonstrate the impact of cultural influences. Additionally, we evaluate how advertising pictures affect Vietnamese consumers' feelings about their families using real-world case studies. In particular, MV Di De Tro Ve seasons 1 and 5 were made to advertise Biti’s Hunter, and MV Di Ve Nha was made to advertise Honda. We will also look at the perspectives of university students on the relationship between cultural values and family connections in Vietnamese advertising. The acquired data were evaluated with SPSS utilizing descriptive analysis and reliability testing. The findings demonstrated the influence of culture on the advertisement's mood component. The use of collectivist culture in Vietnamese advertising can evoke family connections evoked by collectivist society. These studies show that the above methods can be used in practice and have an impact on advertising with a wide audience.
Keywords: emotion, emotional appeal, advertising, cultural value, Vietnamese advertising, collectivist culture